A walk accessibility-based approach to assess crowd management in mass religious gatherings. (October 2022) - Karthika, P.S.; Kedar, Vedankur; Verma, Ashish
Abstract: The effectiveness of any crowd management plan is constrained by the behavior of individuals in the crowd. In mass religious gatherings, the strict time schedules to perform specific activities and the arrival and departure constraints force pilgrims to incorporate multiple stops in the same tour based on the proximity of these sub-destinations. This paper explores the role of accessibility of prime activity locations, possible trip chaining patterns, and the resultant shortest paths in the context of crowd management. The extracted mean speed of pedestrians from the video data of Kumbh Mela, Ujjain (2016) is used as an input to generate the spatial time-based accessibility map. Two methods – space syntax and accessibility considering travel time are used to understand the pilgrim's travel choices. The findings from the study confirm that both distance and directions are the major determinants of pedestrian route choice in mass religious gatherings. The study also evaluates the effect of temporary road closures on the route choices of pilgrims The methodology adopted, and insights derived from the analysis could be used to manage the crowd more effectively by ensuring that critical attention is given to the routes that are more likely to carry the diverted pedestrians during road closures. Highlights: We proposed a framework incorporating two measures of accessibility to assess crowd management strategies. Effect of temporary road closures on roads connecting three prime activity locations in Kumbh Mela, Ujjain was analyzed. Mahakleshwar Temple-Harisiddhi Chauraha link possesses the highest accessibility with a low mean number of turns. Pedestrians minimize both distance and angular distance in their route choices while accommodating multiple stops in tours. Need to consider trip chaining patterns and proximity of sub-destinations prior to impromptu decisions to manage crowd.